Exploring determinants of Indonesia's financial inclusion level: Based on 2017 Global Findex data - Susilowati, Indah; Fikri, Muhammad Kanzul; Sari, Devy Mayang; Razak, Abdul; Khasanah, Uswatun; Djatayu, Mentari Anggun; Suciati, Ika (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2024)
This research aims to analyze the influence of income level, education level, gender, and age level on the three main indicators of financial inclusion, namely the probability of having an account at a formal financial institution, the probability of saving at a formal financial institution, and the probability of borrowing from a formal financial institution in Indonesia on 2017. Data was obtained from Global Findex 2017 using a purposive sampling method. This research uses a logistic regression analysis method with an assisted logit estimation model using Stata 16 software. The research results show that when estimating the probability of account ownership levels at formal financial institutions, only the variable gender shows insignificant results. In contrast, the other variables show significant negative values. In the model for estimating the probability of saving at formal financial institutions, two variables are not significant, namely age and gender, while other variables show significant negative results. Finally, on the probability of borrowing from formal financial institutions, only the basic education level variable shows significant negative results, while the other variables show insignificant results. The implications of this research provide insight into income, education, gender, and age and their impact on financial inclusion.